2019
DOI: 10.32674/jis.v9i1.279
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Ethnic Self-Disclosure Buffering Negative Impacts of Prejudice on International Students' Psychological and Social Well-Being

Abstract: Intergroup contact theory suggests that developing a close relationship with outgroup members ameliorates the negative impact of prejudice that individuals perceive from outgroup members. This article specifically investigates the moderating role of cross-ethnic self-disclosure in the link between international students’ perceived ethnic/racial prejudice and depression as well as loneliness. One hundred and forty-three international students in Japan were asked to rate their perceived prejudice, depression, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 44 publications
1
8
0
1
Order By: Relevance
“…So it validates our hypothesis. This result is consistent with previous foreign research results from Franzoi et al ( 23 ) and Imai and Imai ( 15 ), both of which show that self-disclosure significantly affects loneliness. Researchers Feng Feng, Zhou Zongkui et al also conducted a study on self-disclosure and loneliness in 2011, which is consistent with the results of this study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…So it validates our hypothesis. This result is consistent with previous foreign research results from Franzoi et al ( 23 ) and Imai and Imai ( 15 ), both of which show that self-disclosure significantly affects loneliness. Researchers Feng Feng, Zhou Zongkui et al also conducted a study on self-disclosure and loneliness in 2011, which is consistent with the results of this study.…”
Section: Discussionsupporting
confidence: 93%
“…For the study on self-disclosure and sense of loneliness, the scholar Imai and Imai observed the moderating effect of cross-ethnic self-disclosure on perceived ethnic bias, depression, and loneliness of foreign students; the result shows that the self-disclosure could buffer the negative effects of prejudice on loneliness and depression ( 15 ). Franzoi et al tested the impact of teenagers' self-disclosure on the sense of loneliness with the structural equation, and the result showed that an individual's self-consciousness has an indirect relationship with the sense of loneliness through the self-disclosure with peers, which means that young people with high self-consciousness would prefer to disclose themselves with peers to reduce the sense of loneliness ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these results call attention to the relevance of intervention programs specifically designed to provide support to international students in reducing the amount of discrimination experienced or for learning how to deal with it. A recent study demonstrated that international students' degree of self-disclosure did alleviate the detrimental impact of the perceived discrimination on loneliness (Imai & Imai, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Various changes may occur during acculturation. Living and studying abroad may involve the loss of social ties, separation from family, and a new friendship network in the host country (Imai & Imai, 2019;Mesidor & Sly, 2016;Patron, 2014;Wilks & Neto, 2016). These modifications may have an impact on the loneliness experienced by international students.…”
Section: Background Acculturation and Adaptationmentioning
confidence: 99%
“…In the meantime, universities also benefit from accepting international students economically, culturally and politically. For host countries, mobile students may be a significant source of income and may contribute to economic and innovation systems [6].…”
Section: Introductionmentioning
confidence: 99%